Alternative Fluids – with a Particular Emphasis on Vegetable Oils – as Replacements of Transformer Oil: A Concise Review - Danikas, M.; Sarathi, R. (Engineering, Technology & Applied Science Research, 2020)
For many decades transformer oil has served as a well-known insulating medium. Its electrical properties, among others, have been studied in length. In recent years, with the increasing concern for the environment, alternative insulating liquids have been proposed. In the context of this concise review, such alternative fluids are investigated. Some conflicting evidence regarding experimental results that still persist are discussed and aspects of vegetable oils in need of further work are pointed out.